Efficacy and safety of antidepressants for the treatment of back pain and osteoarthritis: systematic review and meta-analysis. (20th January 2021) - Ferreira, Giovanni E; McLachlan, Andrew J; Lin, Chung-Wei Christine; Zadro, Joshua R; Abdel-Shaheed, Christina; O'Keeffe, Mary; Maher, Chris G
Abstract: Objective: To investigate the efficacy and safety of antidepressants for back and osteoarthritis pain compared with placebo. Design: Systematic review and meta-analysis. Data sources: Medline, Embase, Cochrane Central Register of Controlled Trials, CINAHL, International Pharmaceutical Abstracts, ClinicalTrials.gov, and the World Health Organization International Clinical Trials Registry Platform from inception to 15 November and updated on 12 May 2020. Eligibility criteria for study selection: Randomised controlled trials comparing the efficacy or safety, or both of any antidepressant drug with placebo (active or inert) in participants with low back or neck pain, sciatica, or hip or knee osteoarthritis. Data extraction and synthesis: Two independent reviewers extracted data. Pain and disability were primary outcomes. Pain and disability scores were converted to a scale of 0 (no pain or disability) to 100 (worst pain or disability). A random effects model was used to calculate weighted mean differences and 95% confidence intervals. Safety (any adverse event, serious adverse events, and proportion of participants who withdrew from trials owing to adverse events) was a secondary outcome. Risk of bias was assessed with the Cochrane Collaboration's tool and certainty of evidence with the grading of recommendations assessment, development and evaluation (GRADE) framework. Results: 33 trials (5318 participants) were included. Moderate certainty evidence showed that serotonin-noradrenaline reuptake inhibitors (SNRIs) reduced back pain (mean difference −5.30, 95% confidence interval −7.31 to −3.30) at 3-13 weeks and low certainty evidence that SNRIs reduced osteoarthritis pain (−9.72, −12.75 to −6.69) at 3-13 weeks. Very low certainty evidence showed that SNRIs reduced sciatica at two weeks or less (−18.60, −31.87 to −5.33) but not at 3-13 weeks (−17.50, −42.90 to 7.89). Low to very low certainty evidence showed that tricyclic antidepressants (TCAs) did not reduce sciatica at two weeks or less (−7.55, −18.25 to 3.15) but did at 3-13 weeks (−15.95, −31.52 to −0.39) and 3-12 months (−27.0, −36.11 to −17.89). Moderate certainty evidence showed that SNRIs reduced disability from back pain at 3-13 weeks (−3.55, −5.22 to −1.88) and disability due to osteoarthritis at two weeks or less (−5.10, −7.31 to −2.89), with low certainty evidence at 3-13 weeks (−6.07, −8.13 to −4.02). TCAs and other antidepressants did not reduce pain or disability from back pain. Conclusion: Moderate certainty evidence shows that the effect of SNRIs on pain and disability scores is small and not clinically important for back pain, but a clinically important effect cannot be excluded for osteoarthritis. TCAs and SNRIs might be effective for sciatica, but the certainty of evidence ranged from low to very low. Systematic review registration: PROSPERO CRD42020158521.